2017
DOI: 10.5468/ogs.2017.60.6.549
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of outcome in IB2 and IIA cervical cancer patients treated with primary concurrent chemoradiation versus radical hysterectomy with or without tailored adjuvant therapy

Abstract: ObjectiveThe aim of our study is to compare the overall survival (OS), progression-free survival (PFS), and treatment-related morbidities between primary concurrent chemoradiation therapy (CCRT) vs. radical hysterectomy (RH) with or without tailored adjuvant therapy in patients with stages IB2 and IIA cervical cancer.MethodsThis was a retrospective study of 113 patients with IB2 or IIA cervical cancer treated with either primary CCRT (n=49) or RH (n=64) with or without tailored adjuvant therapy between 2002 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…A seven-study meta-analysis by Yan et al [ 16 ] revealed that ARH had obvious advantages over chemoradiotherapy for IB2-IIA CC. Jang et al [ 17 ] conducted a study on FIGO 2009 IB1-IIA CC and found that the oncological prognosis of ARH was significantly superior to that of concurrent chemoradiotherapy (CCRT). Bansal et al [ 18 ] analyzed 4,885 cases of FIGO 2009 IB1-IIA CC and found that when the tumor diameter is < 6 cm, ARH potentially benefits patient survival more than R-CT; when it is > 6 cm, the two are equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…A seven-study meta-analysis by Yan et al [ 16 ] revealed that ARH had obvious advantages over chemoradiotherapy for IB2-IIA CC. Jang et al [ 17 ] conducted a study on FIGO 2009 IB1-IIA CC and found that the oncological prognosis of ARH was significantly superior to that of concurrent chemoradiotherapy (CCRT). Bansal et al [ 18 ] analyzed 4,885 cases of FIGO 2009 IB1-IIA CC and found that when the tumor diameter is < 6 cm, ARH potentially benefits patient survival more than R-CT; when it is > 6 cm, the two are equivalent.…”
Section: Discussionmentioning
confidence: 99%